Relationship between Health-Related Quality of Life and Social Support in HIV-Infected People in Tehran, Iran - CHARKHIAN, Amir (Iran J Public Health, 2014)
BACKGROUND: The present study was conducted to determine the association between social support and health-related QOL (HRQL) for a sample of 120 patients living with HIV/AIDS in Tehran. METHOD: Eighty male and 40 female living with HIV referred to Iranian AIDS Research Center at Imam Khomini Hospital in Tehran, Iran in 2011 were randomly selected for assessment. Data was collected by means of Vaux's Social Support questionnaire and Medical Outcomes Short-Form-36 (SF-36) QOL questionnaires. Pearson (P) Correlation Coefficient and Fisher z-test were used for statistical analysis. RESULTS: In general, social support was significantly associated with overall QOL in men (P = 0.001) and women (P = 0.009) living with HIV/AIDS. In men, social support was significantly associated with mental and physical domains of QOL (P = 0.001) while in women it simply associated with mental domain of QOL (P = 0.003). CONCLUSIONS: Our findings indicate that increasing social support for HIV/AIDS persons increases their QOL. This can help those physicians who are involved in care of HIV-infected persons and it maintains QOL across the spec-trum of HIV disease.